ASPECTS OF COGNITIVE INTERACTION IN THE SCIENTIFIC COMMUNICATION PRACTICE - O. D. Shipunova; I. P. Berezovskaya (Дискурс)
The article considers cognitive aspects of communicative practice in science that relate to scientific knowledge systematization and transfer. The idea of interactive domains is developed. Interactive domains register the conceptual matrix of information exchange in different forms of scientific practice. The authors identify specific features of cognitive exchange under the influence of intellectual fashion and multimedia space. The constructive role of epistemological attitude concerning case studies is emphasized when disciplinary knowledge creates a terminological barrier and background knowledge becomes essential in the scientific communication. The basic role of causal model in the construction of modern scientific discourse is shown.